A “Golden Age” Puzzle with Female Audiences of Yeşilçam: Nostalgia, Melodrama and Gender - Aynülhayat Uybadın (İnsan & Toplum)
This study focuses on the ways in which the feeling and rhetoric of nostalgia are constructed and made sense of on the basis of the memories of women who went to the movies in the 1960s and 1970s and who watched mostly Yeşilçam melodramas. Experiencing cinema and going to the movies with diverse goals and meanings, these female audiences of Yeşilçam not only provided information about the cinema practices of the past when talking about their memories, but also expressed their feelings, desires and beliefs related to the past. Looking at memories of female cinema audiences suggests looking at the structures of feeling involved in the transformation of experience to memory, and of memory to history in the relationship between the individual and the collective. In line with this suggestion, this article analyzes the feelings of nostalgia in the narratives of historical female audiences by using oral history methods, which I call the myth of the “golden age” and “desire for wooden chairs”, within the framework of experiences and memories of cinema. The analysis shows that female audiences (as historical screen audiences) construct an ambivalent narrative between sense of nostalgia and anti-nostalgia when they recall memories of Yeşilçam melodramas, and sheds light on how women experience and make sense of nostalgia in different ways.